Managing decentralized supply chain using bilevel with Nash game approach. (1st September 2020) - Haque, Marjia; Paul, Sanjoy Kumar; Sarker, Ruhul; Essam, Daryl
Abstract: This paper considers a multi-echelon, non-cooperative and competitive decentralized supply chain (SC) network consisting of multiple entities. The independent and disjointed entities of a decentralized SC face a major challenge in coordination and maintaining sustainability across its chain. This problem environment is not suitable with traditional monolithic modeling approaches. In this paper, a new bilevel approach is proposed, where each entity prepares a plan for multiple periods, on a rolling horizon basis, by optimizing its own objectives at the lower-level. However, due to limited information sharing between the entities from the lower-level, the dominance and Nash game strategies are applied at the upper-level, for coordinating the supply and demand in a single period. It is expected that the upper-level coordination and planning will be conducted by an independent body. The approach applies a strategy to ensure carbon reduction in transportation, by reducing the required number of vehicles to distribute the products throughout the SC. To demonstrate the usefulness of the approach, numerical analysis is provided with examples. The results of the proposed model are compared with two different approaches. A sensitivity analysis is also conducted with some of the major parameters of the model. The main contribution of this study is to ensure coordination in product distribution quantities throughout a decentralized SC network, to minimize carbon emissions through transportation, and to improve SC sustainability.